MBRS-21. EXTRACELLULAR VESICLES FROM METASTATIC MEDULLOBLASTOMA CELL LINES CARRY mRNAs KNOWN TO CORRELATE WITH METASTATIC DISEASE. Issue 2 (22nd June 2018) - Jackson, Hannah K; Linke, Franziska; Kerr, Ian D; Coyle, Beth
Abstract: There is no curative treatment for patients with metastatic medulloblastoma, which is underdiagnosed by current techniques. To improve diagnosis and treatment a greater understanding of the mechanisms of metastasis is required, as is the development of novel diagnostic methods. Extracellular vesicles (EVs) are a heterogeneous population of nano-sized, cell derived vesicles. EVs have been shown to transfer oncogenic proteins and nucleic acid cargo to recipient cells, which modulates their activity and plays a decisive role in tumorigenesis. We hypothesised that EVs play a role in medulloblastoma metastasis. An ultracentrifugation isolation method was optimised to selectively isolate EVs from medulloblastoma cell lines (DAOY, UW228-3, CHLA-01-MED, CHLA-01R-MED, HD-MB03 and D283). Validation was by nanoparticle tracking analysis, transmission electron microscopy and western blotting. The RNA cargo of the isolated EVs was analysed for the expression of metastasis-associated genes c-Met, ABCB1, MMP2, BSG and ITG-A9 by qRT-PCR. Immunofluorescence is also being used to localise MMP2 and EMMPRIN (BSG) encoded proteins. Our data demonstrates that medulloblastoma cells secrete two distinct populations of EVs, exosomes and microvesicles, with unique size, morphology and cargo. We have shown that metastatic cell lines produce significantly higher quantities of exosomes compared with non-metastatic cell lines. Finally, we have identified that candidate metastatic mRNAs; c-Met, ABCB1, MMP2, BSG, and ITG-A9 are present in EVs. This study provides new insights on medulloblastoma EVs. Our results indicate that mRNA of metastasis-associated genes is passed from the parent cells to EVs. Thus, EVs are potential diagnostic and therapeutic biomarkers for medulloblastoma patients.